The Controversy of the Tombs of Religious Figures in Banten: A Study of the Commodification of the Tombs of Religious Figures - Muttaqien, M. Zainul (Green Publisher Indonesia, 2025)
This study examines the commodification of revered religious tombs in Banten, Indonesia, focusing on the tombs of Sheikh Nawawi al-Bantani and Sheikh Abdul Muhyi. As sacred sites increasingly transform into tourist destinations, tensions arise between spiritual values and economic interests. Using a qualitative approach—including in-depth interviews, participant observation, and document analysis—the research explores the drivers of commodification (e.g., rising pilgrimage tourism, social media influence, weak regulations) and its socio-cultural consequences. Findings reveal divergent local perspectives: some communities embrace economic benefits, while others resist commercialization to safeguard spiritual integrity. Unique to Banten, grassroots initiatives like sharia-compliant businesses and religious education programs emerge as countermeasures. The study contributes to broader debates on sacred site management by highlighting the intersection of Islamic tradition, informal governance, and digital-era commodification. It calls for policy frameworks that balance economic development with cultural preservation, offering insights for sustainable religious tourism in similar contexts.